Singing to Estranged Lovers: Runa Relations to Plants in the Ecuadorian Amazon - Swanson, Tod Dillon (Journal for the study of religion, nature and culture, 2009)
This article examines Runa relation to plants in the Ecuadorian Amazon. By examining ritual songs to plants as well as gardening behavior it argues that plants are treated like dangerous lovers or difficult children. To find out why this should be the case it then examines Quichua and Shuar language accounts of the origins of plant species. These accounts suggest that plant species evolve from a previously human state in which the plants were lovers or children who became estranged. The emotional estrangement then hardened into a physical transformation giving rise to a new species. Under certain circumstances plants continue to be treated as though they were moody estranged children or lovers. The paper concludes by suggesting that treating plants as high maintenance lovers leads to a kind of gardening that is more costly in terms of time and dedication than many women can afford under conditions of modernity.